Recyclable polyurethane adhesive, its preparation method and application
Patent Information
- Application Number
- CN202310622924.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-05-30
AI Technical Summary
[0005]本发明的目的在于,克服现有的电池用粘结剂在回收时难以剥离,以及导热率、阻燃性、粘接性无法同时提高的缺陷,提供一种同时具有高导热率、高阻燃性、高粘接性且可回收的粘结剂
本发明通过在聚氨酯分子链段中引入可逆共价键实现了聚氨酯粘结剂的回收再利用;且可逆共价键、聚酯或聚醚链段、羧基基团之间共同作用,提高了聚氨酯粘结剂与金属基材的粘接性能;此外,磷酸酯链段的引入不仅可以与特有可逆键协效提高聚氨酯的阻燃性能,还能与特殊结合的导热填料包裹空心玻璃微珠共同作用,进一步提高了聚氨酯的耐热性能,并且可以在较少的导热填料的添加量下,使聚氨酯胶粘剂获得更高的导热率。
Smart Images

Figure SMS_95 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a recyclable polyurethane adhesive, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries are a new type of high-energy battery. Due to their advantages such as high energy, high voltage, and wide operating temperature range, they have been widely used in aerospace, energy storage devices, and electric vehicles. Currently, lithium-ion power battery packs mainly use adhesives to bond, fix, and assemble multiple stainless steel or aluminum-encapsulated cells together. This often makes it difficult to peel off the adhesives during cell recycling, and also makes it difficult to effectively remove and recycle them.
[0003] Furthermore, binders used in batteries need to possess high thermal conductivity, high flame retardancy, high bond strength, and impact resistance to improve the safety and reliability of power batteries, extend their service life, and cope with more complex working environments. However, to achieve high thermal conductivity and flame retardancy, a large amount of inorganic thermally conductive fillers and flame retardants are generally required, which can easily lead to a deterioration in the adhesive's bonding performance.
[0004] Therefore, there is a need to provide an adhesive that simultaneously possesses high thermal conductivity, high flame retardancy, high adhesion, and is recyclable. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing battery adhesives, such as difficulty in peeling them off during recycling and the inability to simultaneously improve thermal conductivity, flame retardancy, and adhesion, and to provide an adhesive that simultaneously has high thermal conductivity, high flame retardancy, high adhesion, and is recyclable.
[0006] Another object of the present invention is to provide a method for preparing the adhesive.
[0007] Another object of the present invention is to provide the use of the binder in the preparation of batteries.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A recyclable polyurethane adhesive comprises the following components in parts by weight: A) Polyurethane reactive monomers 1-10 parts of a diol monomer containing a reversible covalent bond; 5-15 parts of diol monomers containing polyester or polyether; 0.3-2.5 parts of carboxyl-containing diol monomers; 1.5 to 6 parts of phosphate-containing diol monomers; 4-12 parts of diisocyanate monomer; B) Catalyst 0.001~0.01 parts; C) 0.05~0.3 parts of polyol crosslinking agent; D) 3-15 parts of hollow glass microspheres wrapped with thermally conductive filler.
[0009] The polyurethane of this invention: 1) Reversible covalent bonds are introduced, which can rearrange the network topology under external stimuli (e.g., light, heat, and water), enabling intrinsic self-healing, solid-phase recovery, solution degradation, injection molding, and extrusion molding. This allows for the peeling and recycling of polyurethane binders in the battery under external stimuli. Simultaneously, the self-adaptive properties resulting from the homolytic splitting-bonding of reversible bonds facilitate a tighter bond between the polymer and the substrate, improving the interfacial adhesion of the polyurethane binder. Furthermore, the boron and nitrogen elements in the unique reversible bond types (e.g., borate ester bonds and imine bonds) can form a synergistic flame-retardant effect with phosphate esters.
[0010] 2) Polyester or polyether segments with good flexibility and appropriate crystallinity are introduced to cooperate with isocyanate hard segments with a certain rigidity. Combined with the synergistic effect of reversible covalent bonds and hydrogen bonds formed in polyurethane molecules, the mechanical strength and fracture toughness of polyurethane adhesives can be significantly improved, so that polyurethane and substrate have good adhesion performance.
[0011] 3) A phosphate ester segment with flame-retardant properties is introduced. The phosphate ester segment is connected to the polyurethane macromolecular segment, resulting in more durable flame retardant properties. There are no compatibility issues, and no migration occurs. It does not adversely affect the mechanical properties of the polyurethane adhesive. At the same time, the inventors of this invention also unexpectedly discovered that the combination of the phosphate ester segment containing biphenyl rings and cyclic O=PO bonds with conventional polyurethane segments can increase the rigidity of the macromolecular chain and the crystallization effect of hard blocks, thereby further improving the heat resistance of the polyurethane adhesive.
[0012] 4) Carboxyl groups are also introduced. Carboxyl groups are polar groups that can form coordination bonds with the metal substrate in the battery, improving the adhesion between the polyurethane adhesive and the metal substrate. At the same time, carboxyl groups can increase the hydrophilicity of the material, which helps the aqueous solution to wet the polyurethane adhesive during solution degradation and improves the effect of aqueous solution degradation. In addition, since the acidic carboxyl groups have a high oxygen content, they can also promote the dehydration of the material to carbon during the combustion of the substrate, and can also catalyze the conversion of CO to CO2, further improving the flame retardant and smoke suppression and detoxification properties of the polyurethane adhesive.
[0013] 5) The thermally conductive filler is wrapped around the surface of the hollow glass microspheres. The hollow glass microspheres not only have a low density, which makes them more fluid in the polyurethane system, but their hollow structure and spatial confinement also facilitate the forced contact of the thermally conductive filler on their surface to form a certain thermal conduction path, further reducing the amount of thermally conductive filler and reducing the impact of the thermally conductive filler on the bonding performance of the polyurethane adhesive.
[0014] This invention achieves the recycling and reuse of polyurethane adhesives by introducing reversible covalent bonds into the polyurethane molecular chain segments. Furthermore, the synergistic effect between the reversible covalent bonds, polyester or polyether segments, and carboxyl groups improves the adhesion performance between the polyurethane adhesive and the metal substrate. The introduction of phosphate ester segments enhances the flame retardant properties of the polyurethane. In addition, the combination of thermally conductive fillers encapsulating hollow glass microspheres creates a synergistic effect, enabling the polyurethane adhesive to achieve higher thermal conductivity with a smaller amount of thermally conductive filler added. The inorganic thermally conductive filler encapsulating the surface of the hollow glass microspheres can further improve the heat resistance of the polyurethane adhesive by adsorbing macromolecular segments and interacting with the phosphate ester segments on the polyurethane chain, thus preventing the attenuation of adhesive strength at high temperatures.
[0015] Reversible covalent bonds can be constructed primarily through reversible addition reactions (e.g., Diels-Alder bonds, urea bonds, thiourea bonds), reversible condensation reactions (e.g., imine bonds, borate ester bonds), redox reactions (e.g., disulfide bonds), and free radical coupling reactions (e.g., alkoxyamines, aromatic pinacols). Among these, condensation-type reversible bonds can achieve reversible hydrolysis equilibrium under water stimulation, providing a green, low-carbon, and environmentally friendly controlled degradation and recycling pathway for crosslinked polymers. Therefore, in embodiments of this invention, the reversible covalent bonds in the diol monomers containing reversible covalent bonds are preferably borate ester bonds and / or imine bonds. Borate ester bonds and imine bonds are hydrolyzable bonds; under water stimulation, they can achieve de-crosslinking of the crosslinked network structure through hydrolysis equilibrium, allowing for recovery in aqueous solutions (e.g., when polyurethane adhesives are placed at 25-50 °C). o (It can be soaked in aqueous solution of C and stirred or sonicated for 24~120h). It has the characteristics of simple operation, no organic solvent, environmental protection and energy saving, and is easy to promote on a large scale. Therefore, the reversible covalent bond is preferably borate ester bond and imine bond.
[0016] It should be noted that, in this invention, the diol monomer containing reversible covalent bonds can be a single diol monomer containing reversible covalent bonds, or it can be a mixture of monomers containing different types of reversible covalent bonds.
[0017] When the reversible covalent bond is a borate ester bond, the diol monomer containing the reversible covalent bond includes at least one of the following structural formulas: , , , , , , , ; When the reversible covalent bond is an imine bond, the diol monomer containing the reversible covalent bond includes at least one of the following structural formulas: , , , , , , , , , , , , , , .
[0018] In embodiments of the present invention, the polyester-containing diol monomer includes at least one of the following structural formulas, where 4≤n≤80, 15≤x+y+z≤100, and the degree of polymerization is within this range. The polyester segment molecular weight and crystallinity are moderate, which can ensure that the polyurethane has high mechanical properties, flexibility and adhesive strength. , , , , .
[0019] In embodiments of the present invention, the polyether-containing diol monomer comprises at least one of the following structural formulas: , , , ; In the formula, 25≤n≤115 and 19≤x+y+z≤90. Within this range, the degree of polymerization is moderate, the molecular weight and crystallinity of the polyether segments are moderate, which can ensure that the polyurethane has high mechanical properties, flexibility and adhesive strength.
[0020] In embodiments of the present invention, the carboxyl-containing diol monomer comprises at least one of the following structural formulas: , , , , , .
[0021] In embodiments of the present invention, the phosphate-containing diol monomer comprises at least one of the following structural formulas: , , , .
[0022] In embodiments of the present invention, the diisocyanate monomer comprises at least one of the following structural formulas: , , , , , , , , , , , , , , .
[0023] In embodiments of the present invention, the polyol crosslinking agent comprises at least one of the following structural formulas: (triethanolamine) (glycerol) , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , (Dihydromyricetin).
[0024] The polyol used as the crosslinking agent is a straight-chain or branched polyol with 3 or more hydroxyl groups. The polyol crosslinking agent is further preferably triethanolamine and / or dihydromyricetin, as both triethanolamine and dihydromyricetin readily form intramolecular or intermolecular hydrogen bonds, which is beneficial for further improving the mechanical strength of the polyurethane adhesive and its adhesion to the metal substrate.
[0025] In embodiments of the present invention, the catalyst includes at least one of dibutyltin dilaurate, stannous octoate, and bismuth neodecanoate.
[0026] In embodiments of the present invention, the diameter of the hollow glass microspheres encapsulated by the thermally conductive filler is 10~100μm. Within this particle size range, they can be stably and uniformly dispersed in the polyurethane matrix without sedimentation or agglomeration, and will not affect the mechanical properties or adhesive properties of the polyurethane adhesive.
[0027] In an embodiment of the present invention, the ratio of the thickness of the thermally conductive filler coating to the diameter of the hollow glass microspheres is (0.001~0.05):1. A suitable coating thickness is beneficial for maximizing the thermal conductivity of the filler. The bulk density of the hollow glass microspheres is 0.1~0.9 g / cm³. 3 Hollow glass microspheres within a suitable density range can promote the formation of more effective thermal conduction pathways in the polyurethane system and will not accumulate at the polyurethane surface interface, thus affecting the bonding performance of the polyurethane adhesive.
[0028] Conventional thermally conductive binders and thermally conductive fillers can all be used in this invention. The thermally conductive fillers include, but are not limited to, at least one of boron nitride, molybdenum disulfide, alumina, aluminum nitride, silicon carbide, and synthetic diamond.
[0029] In an embodiment of the present invention, the hollow glass microspheres encapsulated by the thermally conductive filler are prepared by a method comprising the following steps: (1) Surface activation of hollow glass microspheres and thermally conductive fillers Hollow glass microspheres were dispersed in an ethanol / water mixed solution, γ-aminopropyltriethoxysilane (KH-550) was added, and the mixture was stirred at 60~70℃ for 5~10 h. After washing with ethanol and drying, amino-modified hollow glass microspheres were obtained. The thermally conductive filler was dispersed in sodium hydroxide alkaline solution and reacted at 110-120℃ for 12-24 hours to activate the surface. After washing with water, the hydroxyl-activated thermally conductive filler was obtained. Then, it was dispersed in an ethanol / water mixed solution, 3-glycidyl etheroxypropyltrimethoxysilane (KH560) was added, and the mixture was stirred at 60-70℃ for 5-10 hours. After washing with ethanol and drying, the epoxy-modified thermally conductive filler was obtained. (2) Disperse amino-modified hollow glass microspheres and epoxy-modified thermally conductive fillers in toluene organic solvent at 100~120 °C. o The reaction was stirred at C for 2-6 hours, and hollow glass microspheres encapsulated with thermally conductive filler were obtained through ring-opening addition reaction between amino and epoxy groups.
[0030] This invention also protects a method for preparing the above-mentioned recyclable polyurethane adhesive, comprising the following steps: According to the stated weight proportions, the polyurethane reactive monomer and catalyst are subjected to a prepolymerization reaction, then a polyol crosslinking agent is added for a crosslinking reaction, and finally hollow glass microspheres wrapped with thermally conductive filler are added, mixed evenly, and dried and cured to obtain the recyclable polyurethane adhesive.
[0031] In an embodiment of the present invention, the prepolymerization time is 10-30 hours; the prepolymerization temperature is 60-80°C.
[0032] The application of the recyclable polyurethane binder in battery manufacturing is also within the scope of protection of this invention.
[0033] Compared with the prior art, the beneficial effects of the present invention are: This invention achieves the recycling and reuse of polyurethane adhesives by introducing reversible covalent bonds into the polyurethane molecular chain segments. Furthermore, the synergistic effect between the reversible covalent bonds, polyester or polyether segments, and carboxyl groups improves the adhesion performance between the polyurethane adhesive and the metal substrate. In addition, the introduction of phosphate ester segments not only synergistically enhances the flame retardant properties of polyurethane with the unique reversible bonds, but also works with specially bonded thermally conductive fillers encapsulating hollow glass microspheres to further improve the heat resistance of polyurethane. Moreover, it allows the polyurethane adhesive to achieve higher thermal conductivity with a relatively small amount of thermally conductive filler added.
[0034] The polyurethane adhesive prepared by this invention has high thermal conductivity, high flame retardancy, high adhesion and recyclability. Specifically, the thermal conductivity is above 1 W / m·K, and can reach as high as 1.31 W / m·K; the flame retardancy is above V0 level; and the adhesion strength at 60℃ is above 8.8 MPa, and can reach as high as 27.1 MPa. Detailed Implementation
[0035] To better illustrate the purpose, technical solution, and advantages of this invention, specific embodiments will be used to further describe the invention below. However, these embodiments do not limit the invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in this invention are conventional reagents, methods, and equipment in this technical field. Unless otherwise specified, all reagents and materials used in this invention are commercially available.
[0036] Example 1 This embodiment provides a recyclable polyurethane adhesive, the preparation method of which includes the following steps: After melting and drying polyester or polyether diol monomers, solvent, diisocyanate monomers, and catalysts are added and reacted for 3-10 hours. Subsequently, diol monomers containing hydrolyzable dynamic reversible bonds, carboxyl-containing diol monomers, and phosphate ester-containing diol monomers are added and reacted for 3-10 hours. Then, polyol crosslinking agent monomers are added and reacted for 3-10 hours. Finally, thermally conductive fillers are added and stirred evenly. After pouring, drying, and curing, the polyurethane is obtained. The specific steps are as follows: (1) Under an argon atmosphere, 10g of polytetrahydrofuran diol PTMEG2000 (number average molecular weight of 2000, n=28) was added to a 250mL three-necked flask. The temperature was raised to 120℃ to melt PTMEG2000, and then the gas was continuously ventilated for 2h to remove trace amounts of water vapor in the reaction system. (2) The temperature was then lowered to 80°C, and 20 mL of N,N-dimethylformamide, 7.9 g of dicyclohexylmethane 4,4-diisocyanate, and 0.005 g of catalyst dibutyltin dilaurate were added. The reaction was continued for 4 h. The temperature was then lowered to 50°C again, and 3.62 g of diol monomer 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol) containing reversible covalent bonds were added. The reaction was continued for 6 h, and then 0.67 g of 2,2-dimethylolpropionic acid and 3.33 g of other chemicals were slowly added dropwise. 6-((bis(2-hydroxyethyl)amino)methyl)dibenzo[c,e][1,2]oxophosphazenecyclohexane 6-oxide was reacted. After the above system continued to react for 6 hours, a cross-linking reaction was carried out with 0.1 g of triethanolamine for 6 hours. Finally, 6.4 g of boron nitride-coated hollow glass microspheres (diameter 80 μm, boron nitride coating thickness to hollow glass microsphere radius ratio 0.0375:1, hollow glass microsphere packing density 0.26 g / cm³) were added. 3 Mix well, pour into a mold, and continue to cure at 60°C for 16 hours to obtain a recyclable polyurethane adhesive.
[0037] 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol) was prepared as follows: Terephthalic acid and a mixture containing 1,2,5-pentanetriol were dissolved in anhydrous tetrahydrofuran, anhydrous magnesium sulfate was added, and the mixture was stirred for 24 h at 35 °C. The solvent was then removed by filtration and rotary evaporation, followed by precipitation in n-hexane to obtain 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol), with the following molecular structure: .
[0038] Boron nitride-coated hollow glass microspheres were prepared according to the following method: (1) Hollow glass microspheres were dispersed in an ethanol / water mixed solution, γ-aminopropyltriethoxysilane (KH-550) was added, and the mixture was stirred at 70°C for 10 h. After washing with ethanol and drying, amino-modified hollow glass microspheres were obtained. The thermally conductive filler was dispersed in sodium hydroxide alkaline solution and reacted at 110-120℃ for 12-24 hours to activate the surface. After washing with water, the hydroxyl-activated thermally conductive filler was obtained. Then, it was dispersed in an ethanol / water mixed solution, 3-glycidyl etheroxypropyltrimethoxysilane (KH560) was added, and the mixture was stirred at 60-70℃ for 5-10 hours. After washing with ethanol and drying, the epoxy-modified thermally conductive filler was obtained. (2) Amino-modified hollow glass microspheres and epoxy-modified thermally conductive fillers were dispersed in toluene organic solvent and stirred at 120°C for 6 h. Hollow glass microspheres coated with thermally conductive fillers were obtained through the ring-opening addition reaction between amino and epoxy groups.
[0039] Example 2 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (1), 10g of polytetrahydrofuran diol PTMEG2000 is replaced by an equimolar amount of polycaprolactone diol PCLD2000 (number average molecular weight of 2000g / mol, x+y=19).
[0040] Example 3 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (1), polytetrahydrofuran diol PTMEG2000 is replaced by an equimolar amount of polyethylene glycol PEG2000 (number average molecular weight of 2000 g / mol, n=45).
[0041] Example 4 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 7.9g of dicyclohexylmethane 4,4-diisocyanate is replaced by an equimolar amount of isophorone diisocyanate monomer.
[0042] Example 5 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 7.9g of dicyclohexylmethane 4,4-diisocyanate is replaced by an equimolar amount of hexamethylene diisocyanate.
[0043] Example 6 This embodiment provides a recyclable polyurethane adhesive, prepared according to the preparation method of Example 1, the difference being that in step (2), 3.62g of 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol) containing borate ester bonds is replaced by an equimolar amount of N,N'-(1,4-phenyldimethylethylene)-bis(2-(2-aminoethoxy)ethanol) containing imine bonds; N,N'-(1,4-phenyldimethylethylene)-bis(2-(2-aminoethoxy)ethanol) containing an imine bond was prepared as follows: Terephthalaldehyde was dissolved in toluene and cooled to 5°C in an ice-water bath. Then, 2-aminoethanol was slowly added dropwise to the solution. The mixture was then refluxed until no water was formed in the separator. The mixture was cooled to room temperature, and the precipitate N,N'-(1,4-phenyldimethylethylene)-bis(2-(2-aminoethoxy)ethanol) was collected by filtration. Its molecular structure is as follows: .
[0044] Example 7 This embodiment provides a recyclable polyurethane adhesive, prepared according to the preparation method of Example 1, except that in step (2), 3.62g of 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol) containing borate ester bonds is replaced with an equimolar mixture of 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol) and N,N'-(1,4-phenyldimethylethylene)-bis(2-(2-aminoethoxy)ethanol) (molar ratio of 1:1).
[0045] Example 8 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference between this embodiment and Example 1 is that in step (2), 0.67g of 2,2-dimethylolpropionic acid is replaced by an equimolar amount of 2-(bis(2-hydroxyethyl)amino)propionic acid.
[0046] Example 9 This embodiment provides a recyclable polyurethane adhesive, prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 3.33g of 6-((bis(2-hydroxyethyl)amino)methyl)dibenzo[c,e][1,2]oxophosphacyclohexane 6-oxide is replaced by an equimolar amount of 6-(2-(3,4-dihydroxypiperidin-1-yl)ethyl)dibenzo[c,e][1,2]oxophosphacyclohexane 6-oxide.
[0047] Example 10 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 0.1g of triethanolamine is replaced by an equimolar amount of dihydromyricetin.
[0048] Example 11 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference between this embodiment and Example 1 is that in step (2), the ratio of the thickness of the boron nitride coating to the diameter of the hollow glass microspheres is 0.006:1, while other parameters remain unchanged.
[0049] Example 12 This embodiment provides a recyclable polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), the diameter of the boron nitride-coated hollow glass microspheres is 10 μm, while other parameters remain unchanged.
[0050] Example 13 This embodiment provides a recyclable polyurethane adhesive, prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), the packing density of the hollow glass microspheres coated with boron nitride is 0.39 g / cm³. 3 Other parameters remain unchanged.
[0051] Comparative Example 1 This comparative example provides a polyurethane adhesive prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 3.62g of 4,4'-(1,4-phenylenebis(1,3,2-dioxaborane-2,4-diyl))bis(but-1-ol) is replaced by an equimolar amount of butanediol, that is, there are no reversible covalent bonds in the polyurethane adhesive matrix.
[0052] Comparative Example 2 This comparative example provides a polyurethane adhesive prepared according to the preparation method of Example 1. The difference from Example 1 is that 0.67g of 2,2-dimethylolpropionic acid is replaced by an equimolar amount of butanediol, that is, the polyurethane adhesive matrix does not contain carboxyl groups.
[0053] Comparative Example 3 This comparative example provides a polyurethane adhesive prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 3.33g of 6-((bis(2-hydroxyethyl)amino)methyl)dibenzo[c,e][1,2]oxophosphazenecyclohexane 6-oxide is replaced by an equimolar amount of butanediol, that is, the polyurethane adhesive matrix does not contain phosphate ester groups.
[0054] Comparative Example 4 This comparative example provides a polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 6.4g of boron nitride-coated hollow glass microspheres are replaced with 6.4g of boron nitride.
[0055] Comparative Example 5 This comparative example provides a polyurethane adhesive prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 6.4g of boron nitride-coated hollow glass microspheres are replaced with 3.1g of boron nitride and 3.3g of hollow glass microspheres.
[0056] Comparative Example 6 This comparative example provides a polyurethane adhesive, which is prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), the amount of boron nitride-coated hollow glass microspheres added is 11g.
[0057] Comparative Example 7 This comparative example provides a polyurethane adhesive prepared according to the preparation method of Example 1. The difference from Example 1 is that in step (2), 6-((bis(2-hydroxyethyl)amino)methyl)dibenzo[c,e][1,2]oxophosphacyclohexane 6-oxide is replaced by an equimolar amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-O-oxide without hydroxyl functional groups, which is added to the polymer matrix of the crosslinking reaction at the same time as the hollow glass microspheres wrapped with boron nitride. That is, the monomer containing phosphate ester is not covalently bonded to the polyurethane segments.
[0058] Performance testing The properties of the polyurethane adhesives obtained in the above embodiments and comparative examples were characterized. The specific test items, test methods, and results are as follows: 1. The tensile properties of the polyurethane adhesive were tested using a tensile testing machine; the solution degradation and recovery of the material were evaluated using gel permeation chromatography (GPC): the polyurethane material prepared in the examples or comparative examples was immersed in an aqueous solution at 50°C and stirred for 120 h, the polymer degradation was observed, the broken polymer fragments were collected, and their molecular weight was tested to evaluate the effect of solution degradation. The results are shown in Table 1 below.
[0059] 2. The thermal conductivity of the polyurethane adhesive was tested using a Hot Disk thermal conductivity tester; the UL-94 flame retardancy rating of the polyurethane adhesive was analyzed using a vertical burning test; and the lap bonding strength of the polyurethane adhesive to aluminum plates at -30℃, 25℃, and 60℃ was tested using a tensile testing machine. The results are shown in Table 1 below.
[0060] Table 1. Test results of the polyurethane adhesives obtained in the examples and comparative examples. The results above show that: The recyclable polyurethane adhesive prepared by this invention possesses high thermal conductivity, high flame retardancy, high adhesion, and recyclability. Specifically: the thermal conductivity is above 1 W / m·K, reaching up to 1.31 W / m·K; the flame retardancy is above V-0; and the adhesive strength at 60℃ is above 8.8 MPa, reaching up to 27.1 MPa. The polyurethane can undergo a certain degree of degradation through hydrolysis of its internal reversible bonds (borate ester bonds and imine bonds) after a period of water immersion and ultrasonic stirring.
[0061] It should be noted that the adhesive before degradation is a cross-linked polymer that cannot be dissolved in water, making it impossible to test its molecular weight.
[0062] Comparing the results of Examples 1-3, the polyurethane materials with added PTMEG or PCLD exhibit superior tensile strength compared to PEG. Comparing the results of Examples 1 and 4-5, rigid diisocyanates such as dicyclohexylmethane 4,4-diisocyanate are more effective in enhancing the tensile strength of the material compared to isophorone diisocyanate monomers or hexamethylene diisocyanate. Comparing the results of Examples 1 and 2, due to the stronger polarity of ester groups compared to ether groups, polyester polyurethane molecular chains are more polar than polyether polyurethanes, resulting in stronger intermolecular interactions and higher bond attraction, thus exhibiting superior adhesive properties. Comparing the results of Examples 1 and 7, the hydrolysis processes of imine bonds and borate ester bonds exhibit a mutually promoting synergistic effect, reducing the molecular weight after degradation. Comparing the results of Examples 1 and 10, the dihydromyricetin crosslinking agent can improve the tensile strength and elongation at break of polyurethane materials through hydrogen bonding and π-π interactions, which is beneficial for further improving the adhesive strength. This is mainly attributed to the coordination effect of the carbonyl group of dihydromyricetin and the residual phenolic hydroxyl group with the aluminum substrate.
[0063] Comparative Example 1 does not contain reversible covalent bonds, so the resulting polyurethane adhesive cannot be degraded and recycled. Moreover, due to the lack of synergistic effect between specific reversible bonds and phosphate ester flame retardants, the flame retardant effect is also reduced accordingly.
[0064] Comparative Example 2 does not contain carboxyl groups, and the resulting adhesive showed a decrease in bonding strength and flammability rating with the substrate. This indicates that the introduction of carboxyl-containing diol monomers increases the content of polar groups in the adhesive, which can form coordination bonds with the aluminum substrate, thereby improving the bonding performance with the aluminum substrate. At the same time, it helps to increase the degree of degradation in aqueous solution and promotes material dehydration during substrate combustion, thus enhancing the flame retardant effect.
[0065] The performance test results of Example 1 and Comparative Example 3 show that diol monomers containing phosphate ester structures can be used as reactive flame retardants to improve flame retardant effects.
[0066] The performance test results of Examples 1 and Comparative Examples 4-6 show that increasing the amount of thermally conductive filler can improve thermal conductivity, but excessive filler is detrimental to tensile strength and adhesive strength. At the same time, compared with ordinary boron nitride, the same amount of boron nitride can achieve better thermal conductivity when wrapping hollow glass microspheres, indicating that the spatial confinement method is beneficial to build a thermally conductive path and reduce the amount of filler.
[0067] The comparison between the results of Example 1 and Comparative Example 7 further demonstrates that, compared with direct blending and dispersion, the covalent bonding of phosphate ester segments and polyurethane segments is beneficial to improving the rigidity of the polyurethane chain and the crystallization effect of hard blocks, thereby improving the heat resistance of the polyurethane adhesive and avoiding the degradation of the adhesive's bonding performance at high temperatures.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A recyclable polyurethane adhesive, characterized in that, The components include the following parts by weight: A) Polyurethane reactive monomers 3.62 to 10 parts of diol monomers containing reversible covalent bonds; 10-15 parts of diol monomers containing polyester or polyether; 0.3-2.5 parts of carboxyl-containing diol monomers; 3.33 to 6 parts of phosphate-containing diol monomers; 7.9-12 parts of diisocyanate monomer; B) Catalyst 0.001~0.01 parts; C) 0.05~0.3 parts of polyol crosslinking agent; D) 3-6.4 parts of hollow glass microspheres encapsulated with thermally conductive filler; In the diol monomer containing reversible covalent bonds, the reversible covalent bonds are borate ester bonds and / or imine bonds; When the reversible covalent bond is a borate ester bond, the diol monomer containing the reversible covalent bond includes at least one of the following structural formulas: 、 、 、 、 、 、 、 ; When the reversible covalent bond is an imine bond, the diol monomer containing the reversible covalent bond includes at least one of the following structural formulas: 、 、 、 、 、 、 、 、 、 、 、 、 、 ; The carboxyl-containing diol monomer includes at least one of the following structural formulas: 、 、 、 、 、 ; The phosphate-containing diol monomer includes at least one of the following structural formulas: 、 、 、 。 2. The recyclable polyurethane adhesive according to claim 1, characterized in that, In the diol monomer containing polyester or polyether: The polyester-containing diol monomers include at least one of the following structural formulas, where 4≤n≤80 and 15≤x+y+z≤100: 、 、 、 ; The polyether-containing diol monomer includes at least one of the following structural formulas, where 25≤n≤115 and 19≤x+y+z≤90: 、 、 、 、 、 、 。 3. The recyclable polyurethane adhesive according to claim 1, characterized in that, The diisocyanate monomer includes at least one of the following structural formulas: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 4. The recyclable polyurethane adhesive according to claim 1, characterized in that, The polyol crosslinking agent includes at least one of the following structural formulas: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 5. The recyclable polyurethane adhesive according to claim 1, characterized in that, The hollow glass microspheres encapsulated by the thermally conductive filler satisfy at least one of the following characteristics: 1) Thermally conductive fillers include at least one of boron nitride, molybdenum disulfide, alumina, aluminum nitride, silicon carbide, and synthetic diamond; 2) The diameter of the hollow glass microspheres wrapped with thermally conductive filler is 10~100μm; 3) The ratio of the thickness of the thermally conductive filler coating to the diameter of the hollow glass microspheres is (0.001~0.05):1; 4) The bulk density of hollow glass microspheres is 0.1~0.9 g / cm³. 3 .
6. A method for preparing the recyclable polyurethane adhesive according to any one of claims 1 to 5, characterized in that, Includes the following steps: According to the stated weight proportions, the polyurethane reactive monomer and catalyst are subjected to a prepolymerization reaction, then a polyol crosslinking agent is added for a crosslinking reaction, and finally hollow glass microspheres wrapped with thermally conductive filler are added, mixed evenly, and dried and cured to obtain the recyclable polyurethane adhesive.
7. The use of the recyclable polyurethane binder according to any one of claims 1 to 5 in the preparation of batteries.
Citation Information
Patent Citations
Intrinsic self-repairing recoverable polyurethane polymer, and preparation method and application thereof
CN106589311A
Low-density organic silicon pouring sealant and preparation process thereof
CN115011306A